Extracellular Volume Fraction Calculated Using Contrast-Enhanced Computed Tomography as a Biomarker of Oxaliplatin-Induced Sinusoidal Obstruction Syndrome: A Preliminary Histopathological Analysis. (14th February 2023) - Kai, Kengo; Hamada, Takeomi; Sato, Yuichiro; Hiyoshi, Masahide; Imamura, Naoya; Yano, Koichi; Ikeda, Takuto; Ichihara, Akiko; Ogata, Shogo; Choijookhuu, Narantsog; Hishikawa, Yoshitaka; Hosokawa, Ayumu; et al.
Abstract : Background . Oxaliplatin (OX)-based chemotherapy induces sinusoidal obstruction syndrome (SOS) in the nontumorous liver parenchyma, which can increase the risk of liver resection due to colorectal liver metastasis (CRLM). The extracellular volume (ECV) calculated from contrast-enhanced computed tomography (CT) has been reported to reflect the morphological change of hepatic fibrosis. The present retrospective study aimed to evaluate the ECV fraction as a predictive factor for OX-induced SOS. Methods . Our study included 26 patients who underwent liver resection for CRLM after OX-based chemotherapy with a preoperative dynamic CT of appropriate quality. We investigated the relationship between the pathological SOS grade and the ECV fraction. Results . Overall, 26 specimens from the patients were graded with the SOS classification of Rubbia-Brandt et al. as follows: grade 0, n = 17 (65.4%); grade 1, n = 4 (15.4%); and grade 2, n = 5 (19.2%). No specimens showed grade 3 SOS. In a univariate analysis, the ECV fraction in grade 0 SOS was significantly lower than that in grade 1 + 2 SOS (26.3 ± 3.4% vs. 30.6 ± 7.0%; P = 0.025). The cutoff value and AUC value of the ECV fraction to distinguish between grades 0 and 1 + 2 were 27.5% and 0.771, respectively. Conclusions . Measurement of the ECV fraction was found to be a potential noninvasive diagnostic method for determining early-stage histopathological sinusoidal injury induced by OX-based chemotherapy.